The pathogenicity and reproduction capability of four entomopathogenic nematode strains on house cricket (Acheta domesticus) in the laboratory condition - Anh, Do Tuan; Chau, Nguyen Ngoc (Academia Journal of Biology, 2016)
It is first time in Vietnam the pathogenicity evaluation and reproduction capacity of four indigenous strains of entomopathogenic nematodes, viz. S-PQ16, S-QTr, H-KT3987 and H-CB3452 on house cricket (Acheta domesticus) were conducted in the labolatory condition. The lethal concentrations for the mortality 50% insect host (LC50) of S-PQ16, S-QTr, H-KT3987 and H-CB3452 strains were 99, 116, 124 and 100 IJs per one cricket, respectively. These lethal concentrations might be relative low and small LC50 values meaning that the high virulence of the epn strains to house cricket. The reproduction capacity of four epn strains in Acheta domesticus was also with high mortality in comparison with other epn strains in Vietnam and in the world. Of these two Heterorhabditis strains, e.g. H-KT3987 and H-CB3452 128.3×103 IJs and two Heterorhabditis strains with 119.6×103 IJs that were higher in comparison with their yields on Galleria mellonella and on some other insect pests. With low lethal concentration and high reproduction capacity these four epn strains to be adapted potential agents for biocontrol of house cricket. In addition, with the high reproduction capacity of epn strain house cricket can used as insect material for epn culturing in vivo in order to restore the toxic actives of the epn strains. In addition, with the available resources and cheap price, the house crickets would be used as a good alternative option for of G. mellonella in maintaining of epn strains for biocontrol of insect pests in Vietnam.   Citation: Do Tuan Anh, Nguyen Ngoc Chau, 2017. The pathogenicity and reproduction capability of four entomopathogenic nematode strains on house cricket (Acheta domesticus) in the laboratory condition. Tap chi Sinh hoc, 39(1): 24-31. DOI: 10.15625/0866-7160/v39n1.8336. *Corresponding author: nguyengochau.iebr@gmail.com. Received 16 May 2016, accepted 20 March 2017